A ten-year surveillance of PCDD/Fs and PCBs in raw milk from bovine, ovine, and caprine farms in a peri-industrial area of southern Italy - Conforti Virginia; Capuozzo Flavia; Dimuccio Michela Maria; Basile Fabrizio; Franco Ettore; Pellegrino Angelo; Bonerba Elisabetta; Dambrosio Angela; Ceci Edmondo; Quaglia Cristiana Nicoletta; Bozzo Giancarlo (Environmental Research, 2026)

Neuroanatomical correlates of peripersonal space: bridging the gap between perception, action, emotion and social cognition - Gianpaolo Antonio Basile; Elisa Tatti; Salvatore Bertino; Demetrio Milardi; Giovanni Genovese; Antonio Bruno; Maria Rosaria Anna Muscatello; Rosella Ciurleo; Antonio Cerasa; Angelo Quartarone; Alberto Cacciola (Brain Structure and Function, 2024)
Peripersonal space (PPS) is a construct referring to the portion of space immediately surrounding our bodies, where most of the interactions between the subject and the environment, including other individuals, take place. Decades of animal and human neuroscience research have revealed that the brain holds a separate representation of this region of space: this distinct spatial representation has evolved to ensure proper relevance to stimuli that are close to the body and prompt an appropriate behavioral response. The neural underpinnings of such construct have been thoroughly investigated by different generations of studies involving anatomical and electrophysiological investigations in animal models, and, recently, neuroimaging experiments in human subjects. Here, we provide a comprehensive anatomical overview of the anatomical circuitry underlying PPS representation in the human brain. Gathering evidence from multiple areas of research, we identified cortical and subcortical regions that are involved in specific aspects of PPS encoding. We show how these regions are part of segregated, yet integrated functional networks within the brain, which are in turn involved in higher-order integration of information. This wide-scale circuitry accounts for the relevance of PPS encoding in multiple brain functions, including not only motor planning and visuospatial attention but also emotional and social cognitive aspects. A complete characterization of these circuits may clarify the derangements of PPS representation observed in different neurological and neuropsychiatric diseases.

A sound understanding of a cropping system model with the global sensitivity analysis - Annachiara Colombi; Marialaura Bancheri; Marco Acutis; Angelo Basile; Marco Botta; Alessia Perego (Environmental Modelling & Software, 2024)

PCDD/Fs and PCBs in hen eggs from a contaminated area in Italy: a 9 years spatio-temporal monitoring study - Orazio Valerio Giannico; Simona Baldacci; Fabrizio Cosimo Basile; Angelo Pellegrino; Francesco Desiante; Ettore Franco; Gianfranco Diletti; Michele Conversano (Food Additives & Contaminants: Part A, 2023)

Mapping the structural connectivity between the periaqueductal gray and the cerebellum in humans - Alberto Cacciola; Salvatore Bertino; Gianpaolo Antonio Basile; Debora Di Mauro; Alessandro Calamuneri; Gaetana Chillemi; Antonio Duca; Daniele Bruschetta; Paolo Flace; Angelo Favaloro; Rocco Salvatore Calabrò; Giuseppe Anastasi; et al. (Brain Structure and Function, 2019)